Evaluasi Implementasi Program Sekolah Ramah Anak di SD Negeri Bertingkat Naikoten dengan Model CIPP (Context, Input, Process Dan Product) - Tallo, Deshiyana Natalia; Foeh, Yonatan; Marlen Angela Daik (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to evaluate the implementation of the Child-Friendly School Program at Naikoten State Elementary School using the CIPP (Context, Input, Process, Product) evaluation model. This program is designed to create a safe, comfortable, enjoyable learning environment, and ensure the fulfillment of children's rights. The research uses an evaluative descriptive approach with data collection techniques in the form of documentation, observation, and interviews. Data analysis is carried out through data reduction, data presentation, conclusion drawn, and recommendation preparation, while data validity is obtained through triangulation of sources and techniques. The results of the study show that in the context aspect, there is a match between the background, objectives, objectives, and curriculum so that the program is considered feasible to be implemented. In terms of input, schools have had most of the supporting resources, including adequate infrastructure and trained educators. In terms of the process, the implementation of the program is effective through anti-violence policies, the formation of an implementation team, and the active involvement of all school residents. In terms of outcomes, most of the program's objectives were achieved, especially in creating a conducive learning environment, strengthening school-parent collaboration, and shaping the character of students. However, aspects of a healthy school environment still need attention. Overall, this program has a positive impact and is recommended to be continued.